Identification of key genes through the constructed CRISPR-dcas9 to facilitate the efficient production of O-acetylhomoserine in Corynebacterium glutamicum - Li, Ning; Shan, Xiaoyu; Zhou, Jingwen; Yu, Shiqin (Frontiers in Bioengineering and Biotechnology, 2022)
O-Acetylhomoserine (OAH) is an important platform chemical for the synthesis of L-methamidophos and L-methionine. It has been produced efficiently in Corynebacterium glutamicum. However, a wider range of key factors had not been identified, limiting further increases in OAH production. This study successfully identified some limiting factors and regulated them to improve OAH titer. Firstly, an efficient clustered regularly interspaced short palindromic repeats/dead CRISPR associated protein 9 (CRISPR-dCas9) system was constructed and used to identify the key genes in central metabolism and branch pathways associated with OAH biosynthesis. Then, the gltA gene involved in TCA cycle was identified as the most critical gene. A sequential promoter PNCgl2698, which showed different transcriptional intensity in different strain growth periods, was used to control the expression of gltA gene, resulting in OAH production of 7.0 g/L at 48 h. Finally, the OAH titer of the engineered strain reached 25.9 g/L at 72 h in a 5-L bioreactor. These results show that the identification and regulation of key genes are critical for OAH biosynthesis, which would provide a better research basis for the industrial production of OAH in C. glutamicum.